Teaching Observational Data Collection to Early Childhood Preservice Educators. (November 2019) - Love, Hailey R.; Horn, Eva; An, Zhe
Making data-based decisions is a pervasive expectation for educators and is linked to improved outcomes for students. Observational data collection for progress monitoring, in particular, can help educators track and support students' progress toward individualized educational goals in inclusive settings. Yet, many educators struggle with data collection. In this study, the authors use a multiple baseline across participants' single-case design to investigate the effectiveness of a data collection intervention on early childhood preservice educators' data collection quality. Preservice educators received data collection templates, instruction, and individualized feedback to improve their ability to collect observational data and use it to inform practice. Preservice educators' participation in the instructional program improved the quality of their data collection; however, continued feedback was necessary for some skills to improve. Implications for preparing early educators to collect and use observational progress monitoring data are discussed.